Linear Transport in Porous Media. Issue 5 (29th July 2021) - Amagai, Kenji; Hatano, Yuko; Machida, Manabu
Abstract: The linear transport theory is developed to describe the time dependence of the number density of tracer particles in porous media. The advection is taken into account. The transport equation is numerically solved by the analytical discrete ordinates method. For the inverse Laplace transform, the double-exponential formula is employed. In this paper, we consider the travel distance of tracer particles whereas the half-space geometry was assumed in our previous paper [Amagai et al. (2020 ). Trans. Porous Media 132:311–331].